Adiponectina como biomarcador preditivo para síndrome metabólica em adultos: uma revisão da literatura - Macêdo, Rosy Daylla Rodrigues (2022)
Metabolic syndrome (MS) refers to a set of factors such as central obesity, systemic arterial hypertension, dyslipidemia (low HDL and high triglycerides) and resistance to insulin action. The diagnosis of this syndrome is based on criteria previously established by international guidelines. In addition to the MS diagnostic criteria, other markers may be altered, such as adiponectin, an adipokine that acts in metabolic processes involving obesity and insulin resistance. However, there is still a gap in the scientific literature regarding to the use of this biomarker as an important predictor of the development of MS. Thus, the aim of this study was to evaluate, through a literature review, whether adiponectin can be used as a predictive marker for the diagnosis of MS. Initially, 4078 articles were found and after the selection steps, following a standardized protocol, six articles were included in this review. In the selected studies was performed the determination of adiponectin concentration in individuals with and without MS in order to assess the relationship of this adipokine with the syndrome, as well as the ability of adiponectin to predict the development of MS. In most of the studies analyzed, a lower concentration of adiponectin was found in individuals with MS. In addition, participants with the lowest concentrations of adiponectin had almost four-fold increased risk of developing MS compared to those with the highest concentrations. Thus it was found a association of adiponectin with MS with the possibility of the usage of adiponectin as a predictive marker of the diagnosis of metabolic syndrome, once its concentrations are higher in people without MS. However, further prospective studies should be carried out to provide more robust data and solve the existing gaps in the literature about the predictive contribution of adiponectin.